Invasive Candidiasis Associated with Adenovirus Pneumonia - Guwani Liyanage; Madhusha Gonapaladeniya; Thushari Dissanayake (Hindawi Limited, 2021)
Invasive Candida infections in immunocompetent children lead to high morbidity and mortality despite available treatment. Candida albicans and Candida parapsilosis are the most common pathogens; however, there are newly emerging pathogenic non-albicans species. Adenovirus accounts for at least 5-10% of respiratory infections in children, and specific serotypes are associated with severe pneumonia. To the best of our knowledge, invasive Candida infection complicating adenovirus-associated pneumonia in immunocompetent children has not been reported previously. Herein, we describe a preschool child with invasive candidiasis associated with adenovirus pneumonia.